2022
DOI: 10.3390/en15145178
|View full text |Cite
|
Sign up to set email alerts
|

Techno–Economic and Risk Evaluation of Combined Cycle Propulsion Systems in Large Container Ships

Abstract: Owing to the stringent regulations on pollutant emissions that are imposed by the International Maritime Organization and increasing fuel prices, there has been significant research on developing cleaner fuels and novel propulsion systems. This study presents a techno-economical and risk assessment method for evaluating alternative propulsion technologies and cleaner fuels as substitutes for heavy fuel oil and two-stroke diesel engines in marine transportation. This analysis was carried out for two different j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The gas turbine was assumed to operate on natural gas and hydrogen, whereas the diesel engine was assumed to run on marine diesel oil. To estimate the emissions of CO 2 and NO x from the diesel engine, we referred to publicly available data and determined that the range of emissions was between 560 and 620 g/kW•h and 8 and 10 g/kW•h, respectively [12,[15][16][17][18]. The gas turbine chosen for the research used a low-NO x combustor that produced low NO x emissions, comparable with those of natural-gas-powered land-based gas turbines [36][37][38][39][40].…”
Section: Environmental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas turbine was assumed to operate on natural gas and hydrogen, whereas the diesel engine was assumed to run on marine diesel oil. To estimate the emissions of CO 2 and NO x from the diesel engine, we referred to publicly available data and determined that the range of emissions was between 560 and 620 g/kW•h and 8 and 10 g/kW•h, respectively [12,[15][16][17][18]. The gas turbine chosen for the research used a low-NO x combustor that produced low NO x emissions, comparable with those of natural-gas-powered land-based gas turbines [36][37][38][39][40].…”
Section: Environmental Resultsmentioning
confidence: 99%
“…Alzayedi [10,17,18] examined a combined cycle fuelled by LNG and marine diesel oil for a large container ship instead of a two-stroke diesel engine. Using numerical software and a TERA approach, the results indicated that LNG was a promising alternative fuel for the marine sector.…”
mentioning
confidence: 99%
“…Using techno-economic evaluation, Wang et al [17] matched different enterprises with feasible and typical integrated energy technologies. Li et al [18] and Alzayedi et al [19] verified the feasibility of the proposed new scenarios and systems, respectively. Based on the application of engineering economic evaluation in engineering projects, Wu [20] further established a related intelligent decision-making system.…”
Section: Introductionmentioning
confidence: 90%
“…[18] and Alzayedi et al. [19] verified the feasibility of the proposed new scenarios and systems, respectively. Based on the application of engineering economic evaluation in engineering projects, Wu [20] further established a related intelligent decision‐making system.…”
Section: Introductionmentioning
confidence: 92%